Pemberian Terapi Musik Klasik Bahasa Inggris dan Murotal Terhadap Penurunan Tingkat Depresi pada Lansia di Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2024 - Zulkarnain Batubara; Rosmega Rosmega; Imran Saputra Surbakti; Indra Septiadi Manurung; Muhammad Hafiz; Hafsah Lubis (Jurnal Nusantara Berbakti, 2025)
Depression is the most common psychological disorder that occurs in the last years of an individual's life. Elderly depression has an impact, including shortening life expectancy by exacerbating physical deterioration in the elderly, hindering the fulfillment of elderly developmental tasks, decreasing the quality of life of the elderly, draining the emotions and finances of the affected person as well as their families and social support systems. Physiotherapist programs provided to the elderly who are depressed include listening to classical music in English and murottal. For this reason, this community service activity aims to socialize the provision of English classical music therapy and murottal to reduce the rate of depression in the elderly. This community service activity uses the method of practical lectures and questions and answers. The lecture method was carried out by delivering material about depression and English music therapy. After that, the practice of listening to English and Murotal classical music, while the question and answer method was carried out by asking participants about the material that had been presented. Results: The results of this community service activity were obtained that participants were able to understand and apply the material that had been delivered. Conclusion: Based on the community service activities that have been carried out, many of the participants enthusiastically received the entire series of events ranging from material presentations, practice listening to English classical music to question and answer interactions.